Distinct inflammatory profile underlies pathological increases in creatinine levels associated with Plasmodium vivax malaria clinical severity - Cruz, Luís A. B.; Barral-Netto, Manoel; Andrade, Bruno B. (PLOS Neglected Tropical Diseases, 2018)
Author summary Severe clinical presentations of Plasmodium vivax malaria are not completely understood. Multi-organ involvement is described in severe vivax cases, however data associating it with kidney dysfunction are relatively scarce, in part because the clinical signs only appear late during kidney injury. We analyzed biomarkers of renal function in groups of patients from the Brazilian Amazon with different presentations of vivax malaria to determine its associations with disease progression. Inflammatory biomarkers were also analyzed to assess inflammation related to kidney dysfunction. The results indicate that severe disease presentation in these patients was associated with abnormal serum creatinine elevations and exacerbated systemic inflammatory response. The highest levels of creatinine were observed in nonsurvivors. Biomarkers of hemolysis did not directly follow increases in serum creatinine. These readouts suggest that kidney dysfunction probably influences vivax malaria severity and mortality. As P. vivax is a widely distributed species of Plasmodium in the world, and severe cases are increasingly being reported, it is important to better understand the role of kidney injury in these presentations, especially considering that it may affect clinical outcomes.